Protocol for assessing digital tools in climate change mitigation research and extension - Ngaiwi, Mary; Vanegas Cubillos, Martha Cristina; Sylvester, Janelle (2023)
The objective of this study is to assess available digital tools that researchers and extension advisers can use to contribute to achieving low-emission food systems and sustainable development priorities and to determine, based on the assessment, what digital tool needs persist.